Fortaleciendo la gestión forestal comunitaria: uso de madera para construcción de viviendas con identidad. Territorio indígena Alto Chirripó - Villalobos-Barquero, Veronica (2025)
The results are the product of the work carried out with the communities of the Alto Chirripó Indigenous Territory, in the district of Chirripó, Cartago, Costa Rica. Fifteen indigenous people were trained in the use of forestry measurement instruments. The training plan, designed in collaboration with community leaders, combined theoretical, practical, cultural and environmental aspects. The participants, together with forestry engineering students from the Instituto Tecnológico de Costa Rica and extensionists, carried out forest inventories and censuses to collect silvicultural data such as diameter, height, species, log quality and tree health. Species such as Copal, Guayabillo, and Robles were highlighted for their potential for housing construction. In terms of current housing and perception of habitability, 56 indigenous families were interviewed. Sixty-five percent of the houses are mainly built with wood. The families showed a preference for wood; in addition to wood, 31% of the families expressed interest in ceramic as a material for their homes, followed by 10% who indicated a preference for prefabricated materials. Finally, 45.2% of those interviewed still prefer the toilet to be located in a space outside the dwelling.